OUTCOME OF RECURRENT MACULAR HOLE CLOSURE WITH AMNIOTIC MEMBRANE PLUG - Saad, Syed Muhammad; Syed Fawad Rizvi; Muhammad Abdullah Tufail Khan; Syed Asaad Mahmood; Sabeen Abbasi; M. Tanweer Hasan Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: The surgery of macular hole is a complex and intricate micro-surgery and chances of recurrence of macular hole are always high. Therefore, in order to provide a medium to close this hole, we carried out this research on subjects using amniotic membrane, in light of the studies being conducted around the world. This in turn led to benefitting the patients by improving their vision over time. Purpose: To assess the rate of recurrent macular hole closure with amniotic membrane plug. It was a Quasi-experimental study, conducted at Layton Rahmatullah Benevolent Trust (LRBT) Free Eye Hospital Karachi, from January 2019 to January 2020. Methods: This study was conducted using 13 eyes of 13 patients with recurrent macular hole who underwent amniotic membrane plugging via pars plana approach. Outcomes measured were changes in best corrected visual acuity (BCVA) and change in hole size with the help of optical coherence tomography (OCT). Results: Anatomic closure was attained in 100% of the cases whereas BCVA improved from 1.7±0.33 (6/300) to 0.9±0.15 (6/48). Conclusion: The use of AM is a functional method for management of large RMH.